The New Zealand’s Recognised Seasonal Employer Policy and the Contractual Rights of Indonesian Workers - Banu, Lukas; Gardiner, Matthew (Udayana Journal of Law and Culture; Vol 2 No 1 (2018): Maintreaming Socio - Cultural Policy, 2018)
The Recognised Seasonal Employer (RSE) scheme has attracted overseas workers to work in the horticulture and viticulture industries in New Zealand. They come from various countries all over the world, to stay and work in New Zealand. This article would explore some legal issues arise from New Zealand’s RSE policy in particular relation with the Indonesian migrant workers who seek a job in New Zealand. It would also analyze the rights and obligations of the workers as stipulated in the employment contract concluded by the Indonesian workers and the New Zealand companies under the RSE scheme. The normative legal writing combines the research on relevant public and private legal instruments and comparatively examines both national law and regulations of Indonesia and New Zealand in order to afford a balanced insight of the law of both countries. This study found that on one hand, New Zealand laws have already covered all aspects of workers and determined New Zealand’s government obligation to oversee the employment agreements, while on the other hand, Indonesian law and regulation do not cover explicitly the issue of protection of Indonesian workers who work in New Zealand under the RSE scheme. This article offers constructive recommendations addressed to any relevant stakeholders in order to improve the legal nature, institutional role and procedure for supporting New Zealand’s RSE policy and in the same time the better protection to the Indonesian migrant workers.